Antinociceptive local activity of 4-allyl-1-hydroxy-2-methoxybenzene (eugenol) by the formalin test: an anti-inflammatory effect - Daniela Elizabeth Lugo-Lugo; Amaury de Jesús Pozos-Guillén; Juan Ramón Zapata-Morales; Antonio Rodríguez-Chong; Azahel de Jesús Rangel-López; María Zenaida Saavedra-Leos; Angel Antonio Vértiz-Hernández (Brazilian Journal of Pharmaceutical Sciences)
Eugenol has been employed for decades as a condiment, an antimycotic, an antibacterial, an antiviral, and an antioxidant, and it is one of the natural analgesics most frequently utilized for pain and inflammation. Our objective was to determine the analgesic/anti-inflammatory effect of eugenol compared with diclofenac, naproxen, and tramadol using the formalin test. The formalin method was used in 6- to 10-week-old Wistar rats (weighing 250 g each) divided into six groups: saline (0.9%); formalin (5%); diclofenac (250 µg/kg); naproxen (400 µg/kg); tramadol (500 µg/kg), and eugenol (1,400 µg/kg), in the intraplantar part of the hind-end trunk of the rats, with n = 5 per group. Eugenol diminished 44.4% of nociceptive behavior in phase 1 and 48% in phase 2 (p ≤0.05 vs formalin). Eugenol was shown to be 1.14 times more effective than diclofenac, but 1.62 and 1.75 times less effective than naproxen and tramadol, respectively, in phase 1 and 1.45 times less effective than diclofenac and naproxen and 1.66 less effective than tramadol in phase 2 (p ≤0.05). These data suggest that eugenol possesses moderate activity in the acute pain phase and greater activity in inflammatory-type pain, and both effects are comparable to those produced by diclofenac and are less than the effects produced by naproxen and tramadol in the formalin test.